ANALISIS KEDISIPLINAN PESERTA DIDIKDENGAN LATAR BELAKANG ORANG TUA MERANTAU - Triyani; Ana Andriani; Wakhudin (Universitas Sebelas Maret, 2026)
The discipline of students with the background of migrating parents is the subject of this research. This study aims to analyze the discipline of students with the background of migrating parents at SD Negeri Adirejakulon, Adipala District, Cilacap Regency. The descriptive qualitative approach with the case study method is the approach and method used in this study. The research subjects in this study are students, parents, and teachers. Data collection techniques through observation, interviews, and documentation. The results of the study show that the attitude of students who have high discipline shows responsibility in carrying out every rule and task given which consists of time discipline, such as being on time in learning, doing assignments according to responsibility, compliance with school rules and discipline of actions, such as obedience to the rules of the game and school activities, neatness and conformity with dress standards, involvement in maintaining order, awareness and self-control. Migrating parents do not carry out their role optimally, especially in terms of providing guidance and assistance. Parental participation is needed to create a conducive learning atmosphere and form positive habits for children.